Antimicrobial properties of glass-ionomer cement incorporated with nano-hydroxyapatite against mutans streptococci and lactobacilli under orthodontic bands: An in vivo split-mouth study - Maryam Shirazi; Aydin Pirzeh; Marzieh Atashgaran (Dental Research Journal, 2024)
Background: Fixed orthodontic appliances enhance dental plaque accumulation. Glass ionomer (GI) is among the most popular orthodontic cement. It possesses antibacterial properties; however, its antibacterial activity may not be sufficient for caries prevention. Although evidence shows that the addition of 8wt% nano-hydroxyapatite (nHA) may enhance the antibacterial properties of GI, no clinical study has been conducted in this respect. Thus, this study aimed to assess the subgingival accumulation of Streptococcus mutans (S. mutans) and Lactobacillus acidophilus (L. acidophilus) around orthodontic bands cemented with conventional GI and GI reinforced with 8wt% nHA. Materials and Methods: This split-mouth clinical trial was conducted on 20 patients requiring a lingual arch. The patients were randomly assigned to two groups. In group 1, the right molar band was cemented with pure Fuji I (GC), and the left was cemented with Fuji I containing 8wt% nHA. In group 2, the right molar band was cemented with Fuji I containing 8wt% nHA, and the left was cemented with Fuji I. After 3 months, subgingival sampling was performed by sterile paper points. S. mutans and L. acidophilus were cultured on MSB and MRS agar, and colonies were counted by a colony counter. Data were analyzed by independent samples t-test using SPSS 25 at a 0.05 level of significance. Results: The mean counts of S. mutans, aerobic and anaerobic lactobacilli, and total bacterial around orthodontic bands cemented with Fuji I containing 8wt% nHA were significantly lower than those around orthodontic bands cemented with pure Fuji I (P < 0.05). Conclusion: The addition of 8wt% nHA to GI cement can enhance its antibacterial properties for the cementation of orthodontic bands, decrease the accumulation of cariogenic bacteria, and probably decrease the incidence of caries in orthodontic patients.